Haemolytic anaemia and bilateral uveitis associated with leptospirosis in a 6‐year‐old Quarter Horse gelding. (11th November 2016) - Delph, K. M.; Sharpe, E.; Beard, L. A.; Rankin, A. J.
Summary: A 6‐year‐old Quarter Horse gelding was presented for bilateral uveitis resulting in vision loss as well as icterus. Anaemia with autoagglutination was consistent with a presumptive immune‐mediated haemolytic anaemia. Urinary PCR was positive for Leptospira spp. and microscopic agglutination test (MAT) titres were elevated to multiple serovars supportive of a diagnosis of leptospirosis. Treatments included broad spectrum antibiotics and aggressive anti‐inflammatory medications. While the horse was hospitalised, the development of bilateral corneal ulcers precluded the use of topical ophthalmic anti‐inflammatories for a number of days. The corneal ulceration resolved, vision returned in both eyes and the immune‐mediated haemolytic anaemia resolved. After 9 days of hospitalisation, oral minocycline was administered for 2 weeks at home as well as low dose oral flunixin meglumine and topical ophthalmic diclofenac and atropine. This case represents the first published case of haemolytic anaemia associated with leptospirosis in a horse.